The Effect of Servant Leadership Style on Organizational Commitment: The Case Study of Ileys Enterprise Detergent Manufacturing Company in Burao, Somaliland - Abokor, Hassan (European Journal of Business and Strategic Management, 2024)
Purpose: This study examined the effect of servant leadership style on organizational commitment in Ileys enterprise detergent manufacturing company in Burao, Somaliland. Methodology: The study employed a cross-sectional survey design, explanatory research, and quantitative approach; the target population was 200 employees working currently at Ileys enterprise detergent in the Burao district. The study used the census method. Data was collected from primary sources using standardized servant leadership style and organizational commitment questionnaires, adapted from previously used standard questionnaires. The study used SPSS for data analysis. Correlation and regression were used to analyze the relationship between servant leadership styles and organizational commitment. Findings: The regression results showed that the types of servant leadership styles have significant contributions to organizational commitment (R = 0.720, p = 0.000). It was concluded that all the servant leadership styles affect employee commitment. In The authenticity dimension of servant leadership was found to be the dominant servant leadership style (β =.557, p =0.000) in the Ileys enterprise. Unique Contribution to Theory, Practice and Policy: The study was used the servant leadership theory. To increase employees’ organizational commitment, manufacturing enterprise should develop training programs or mentoring by professionals for the supervisors and leaders that support servant leadership development. The study recommended that private manufacturing enterprises could practice the information to help develop strategies and meet organizational needs through servant leadership behavior development